The Status of Arabic Social Psychology: A Review of 21st-Century Research Articles. Issue 7 (September 2020) - Saab, Rim; Ayanian, Arin H.; Hawi, Diala R.
This article explores the current state of Arabic social psychology through a selective review of articles written by Arabs, on Arabs, in Arabic (144 articles, published between 2000 and 2015), a basic profiling of first authors, and a regional mapping of graduate social psychology programs. The Levant emerged as the most productive subregion. The most studied topics overall were "the self" and "social adjustment." Most articles relied primarily on regional references. Furthermore, articles were mostly empirical, correlational, with adult samples, particularly university students. Most first authors were males and very few were specialized in social psychology. Finally, very few graduate social psychology programs were found. We discuss some ways forward for addressing the seemingly marginalized state of social psychology in the Arab region.